Mineral and heavy metal contents of marine fin fish in Langkawi Island, Malaysia - Jaswir, Irwandi; Osman, Farida (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2009)
A study was conducted to quantitate the concentrations of heavy metals, such as Hg, Pb and Cd in eight species of marine fin fish caught off the coast of Langkawi Island in Malaysia, as well as in its waters. The same fish were also used to determine the content of nutritional minerals, such as copper (Cu), zinc (Zn), calcium (Ca), and manganese (Mn). Fish and water samples were collected from four different areas, namely (1) Main Jetty Pulau Tuba (MJPT), (2) Teluk Cempedak Jetty (TCJ), (3) Simpang Tiga Chian Lian (STCL) and (4) Main Jetty Kuah (MJK) around Langkawi Island. Results showed that for the vital elements, all species had higher concentration of Zn compared to other elements. For the toxic elements, lead (Pb) and mercury (Hg) were found to have lower concentration of the mean values than the permissible limits set by FAO/WHO (1984). However, cadmium (Cd) level was slightly higher than the permissible limit but was still acceptable according to the Malaysian Food Regulation (1985). It can be concluded that all fish species studied are safe to be consumed.